2023
DOI: 10.31602/jssi.v1i1.9700
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Monitoring, Keuangan, Penjualan, Pembelian Dan Mortalitas Ayam Broiler Berbasis Web Pada Pt. Rainbow Rehobot

Abstract: PT. Rainbow Rehobot adalah perusahaan swasta yang bergerak di bidang peternakan ayam broiler didaerah kalimantan. Hingga saat ini PT. Rainbow Rehobot masih menggunakan semi manual dalam melakukan pengolahan data perusahaan, dimana data yang ada masih dicatat dibuku atau dikertas serta membuat laporan masih menggunakan MS.Word dan MS. Excel, proses pencariandata juga masih terbilang sulit karena informasi tidak didokumentasikan dengan baik. Adanya Aplikasi Monitoring, Keuangan, Penjualan, Pembelian dan Mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Wulandari et al (2022) addressed the time-consuming nature of manual data recording in free-range chicken farming with an application that streamlined various data aspects including costs and profit-loss reports [13]. Melisa et al (2023) observed the issues of data loss and inaccuracy in manual poultry farm recording systems, leading to the development of an application for efficient and accurate recording of sales, purchases, and mortality data [14]. Lastly, Werdiningsih et al (2023) contributed by developing an application for recording and graphically reporting chicken egg data, enhancing data visualization and management [15].…”
Section: Introductionmentioning
confidence: 99%
“…Wulandari et al (2022) addressed the time-consuming nature of manual data recording in free-range chicken farming with an application that streamlined various data aspects including costs and profit-loss reports [13]. Melisa et al (2023) observed the issues of data loss and inaccuracy in manual poultry farm recording systems, leading to the development of an application for efficient and accurate recording of sales, purchases, and mortality data [14]. Lastly, Werdiningsih et al (2023) contributed by developing an application for recording and graphically reporting chicken egg data, enhancing data visualization and management [15].…”
Section: Introductionmentioning
confidence: 99%